Market Leader : intermediate business english cource book [ - COTTON, David; Falvey, David; Kent, Simon (Harlow, England ; New York: Pearson Education / Financial Times Prentice Hall, 2014)
Window XP/Vista/7. Mac OSX 10.4 to 10.6 Linux Ubuntu 8.04 to 10.04 1GHz Processor
To accompany with textbook titles "Market Leader : intermediate business english cource book / David Cotton, David Falvey, Simon Kent"
MBA
PHD
Keywords: English language -- -- Business English